Experimental investigation on heat transfer performance of corrugated low finned tubes. Issue 1 (April 2020) - Ren, Bin; Si, Jun; Tang, Xiaoying; Lu, Hongliang; Du, Yannan; Ren, Facai
Abstract: With the outbreak of oil crisis, heat exchangers as the energy-saving devices have gained more and more attentions. The heat transfer enhancement techniques have been developed to the third generation. Corrugated low finned tube is a kind of helically corrugated tube with trapezoidal shape groove. In this paper, the performance of convective heat transfer inside corrugated low finned tubes was studied experimentally. The results showed that the heat transfer performance could be intensified compared with the smooth tube. The reason was that helical rib generated the secondary flow and longitudinal vortex, reducing the synergy angle between velocity vector and temperature gradient. Moreover, the effects of tube structural parameter and fluid Reynolds number were analyzed. Finally, all the experimental data were fitted as the function of Reynolds number, Prandtl number, tube pitch and rib height. The research results can provide a foundation for designing heat exchangers using this enhancement technique.